Design basics for creative results - Peterson, Bryan L., 1953- (How Design Books, 2003)
Through informative tutorials and illuminating exercises, award-winning designer Bryan L. Peterson shows you how to express and anchor your concept with the design elements of line, type, shape, texture, balance, contrast, unity, color and value.